COMPLETION OF RATING ON THE SYSTEM OF SOCIAL PARTNERSHIP AT OIL ENTERPRISES IN THE REPUBLIC OF KAZAKHSTAN - Sansyzbayev Alisher; Kenzhalina Zhanna; Malgaraeva Zhanat (Academic Journal of Physical and Chemical Sciences, 2020)
This article presents the results of the analysis of the state of labor relations at modern oil and gas enterprises in Kazakhstan, as well as the trends in their changes under the influence of modernization processes. It justifies the approach to social partnership as one of the modern conditions (forms) of labor relations, which continues to change its content under the influence of production modernization processes in the oil and gas sector. The possibility of assessing the state of labor relations and the compliance of labor process participants with the requirements that modernization of the technical foundations of production presents is considered. A description is given of a methodology that allows us to assess the involvement of workers in the activities of the enterprise, as well as the state of formation of social partnership. The relevance of the study is that today, the role of social partnership is increasing because of the steady increase of conflict and competition levels in enterprises as a result of global inflation and crisis phenomena. The level of loyalty, peace of mind at the enterprise depends on the implementation of the principles of social partnership, the action of concluded industry and collective agreements. Oil-producing enterprises remain the flagship of the development of the entire national economy and represent an export-oriented industry. The scientific research method is the qualitative analysis, comparative analysis, application of the rating approach and ranking of results. As a result of the conducted research, based on the analysis of a number of indicators of companies that affect the level of social partnership, the problems of its development were clearly identified. In the course of the analysis, indicators that reflect the level of development of social partnership were grouped, a rating of companies was compiled according to the level of development of social partnership. Based on the calculation of the total rating, a final rating was compiled. The relationship between the final rating of social partnership companies and indicators of social and labor relations is considered. This article can be useful in case of the methodological and normative documents developments on social partnership, in particular, in case of concluding a General Agreement between employers, trade unions, and representatives of employers, when concluding industry tariff agreements, collective agreements, and also in event of a strategy development for oil companies to further avoid labor conflicts.